2022
DOI: 10.3389/fpsyg.2022.976330
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated learning strategies of Macau English as a foreign language learners: Validity of responses and academic achievements

Abstract: Self-regulation is important in enhancing students’ academic performance, yet evidence for the systematic and valid instruments to measure self-regulated learning strategies of college students in an English as a foreign language context is far from robust. This study was situated to develop an evaluation tool to examine the status quo of self-regulated learning strategies employed by college English learners and the associations between the use of these strategies and their academic achievement. A large-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…It also points that academic accomplishment is more immediately impacted by SRL since it entails the capability to directly monitor a learning setting and make adjustments to boost learning efficacy (Wang & Kao, 2022). (Deng et al, 2022) also reported that self-regulated learning takes significant role on students' academic performance in Macau. (Olakanmi et al, 2017) draw a conclusion that self-regulated learning has significant part in increasing students' academic performance.…”
Section: Metacognition and Self-regulated Learning As Predictors Of A...mentioning
confidence: 99%
“…It also points that academic accomplishment is more immediately impacted by SRL since it entails the capability to directly monitor a learning setting and make adjustments to boost learning efficacy (Wang & Kao, 2022). (Deng et al, 2022) also reported that self-regulated learning takes significant role on students' academic performance in Macau. (Olakanmi et al, 2017) draw a conclusion that self-regulated learning has significant part in increasing students' academic performance.…”
Section: Metacognition and Self-regulated Learning As Predictors Of A...mentioning
confidence: 99%
“…However, traditional language learning methods, such as classroom-based instruction, may not be suitable for everyone. Some learners prefer a more personalized and flexible approach to language learning, where they can learn at their own pace, focus on areas that are relevant to them, and use resources and materials that suit their individual learning style (An et al, 2021;Deng et al, 2022;Tomak & Seferoğlu, 2021). Self-regulated learners know their learning processes and use self-correction to attain desired results (Zimmerman et al, 1996).…”
Section: Diy English Language Learningmentioning
confidence: 99%
“…However, L2 writing is also one of the most challenging skills, as it is “recursive, strategic, and multidimensional” (p. 188) [ 7 ]. It also varies among groups of EFL learners and across a wide range of EFL contexts [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%